Pure spinor partition function using Padé approximants - Arroyo, E. Aldo [UNESP] (Int School Advanced Studies, 2008)
In a recent paper, the partition function (character) of ten-dimensional pure spinor worldsheet variables was calculated explicitly up to the fifth mass-level. In this letter, we propose a novel application of Padé approximants as a tool for computing the character of pure spinors. We get results up to the twelfth mass-level. This work is a first step towards an explicit construction of the complete pure spinor partition function.
Keywords: Superstrings and heterotic strings; Topological strings